Control-Analytical Procedures in the Public Health System in the Context of Digitalization - D. A. Endovitsky; N. V. Kondrashova; S. V. Golovin; A. V. Churikov (Учёт. Анализ. Аудит)
Economic analysis, including its methodological tools, is necessary for organisations of various fields of activity and forms of ownership. A wide range of analytical techniques, the universality of their application and other economic sciences and modern management practice also contributes to the active interpenetration and differentiation of analysis. of the object’s economy, becomes a methodological basis for various types of control, and applying its methodology in a control measure turns it into a control-analytical procedure. We based our research on the study of economic literature concerning theoretical provisions and applied developments in the field of economic analysis and control of the activities of public medical organisations. We used methods of generalisation, systematisation, grouping, methods of economic analysis in the research process. The result of the study was a set of the following conclusions and results: Identification of new types of economic analysis generates new types of analytical work, including economic analysis in the control.Based on the general methodological basis of economic analysis and control, together with the universality of the methodological apparatus of economic analysis, the authors developed a typical structure of the control methodology.We considered analytical procedures in the implementation of control as the content of the partial fulfilment of the control procedure of the methodology of the object of control.Control and analysis depend on the time of their conduct, but with a similar essential characteristic, their volume and depth of conduct are different.The implemented digitalisation tools will significantly increase the scope of applying control-analytical procedures.